Sirtuin-dependent metabolic and epigenetic regulation of macrophages during tuberculosis - Zhang, Kangling; Sowers, Mark L.; Cherryhomes, Ellie I.; Singh, Vipul K.; Mishra, Abhishek; Restrepo, Blanca I.; Khan, Arshad; Jagannath, Chinnaswamy (Frontiers in Immunology, 2023)
Macrophages are the preeminent phagocytic cells which control multiple infections. Tuberculosis a leading cause of death in mankind and the causative organism Mycobacterium tuberculosis (MTB) infects and persists in macrophages. Macrophages use reactive oxygen and nitrogen species (ROS/RNS) and autophagy to kill and degrade microbes including MTB. Glucose metabolism regulates the macrophage-mediated antimicrobial mechanisms. Whereas glucose is essential for the growth of cells in immune cells, glucose metabolism and its downsteam metabolic pathways generate key mediators which are essential co-substrates for post-translational modifications of histone proteins, which in turn, epigenetically regulate gene expression. Herein, we describe the role of sirtuins which are NAD+-dependent histone histone/protein deacetylases during the epigenetic regulation of autophagy, the production of ROS/RNS, acetyl-CoA, NAD+, and S-adenosine methionine (SAM), and illustrate the cross-talk between immunometabolism and epigenetics on macrophage activation. We highlight sirtuins as emerging therapeutic targets for modifying immunometabolism to alter macrophage phenotype and antimicrobial function.